Marketing Strategy Analysis and Product Innovation making added value Bitter Melon - Ula, Rizal (Jurnal Keuangan dan Bisnis, 2020)
Habits of people who like snacking (light meals), making business opportunities for some people, supported by many of bitter melon fruit in the district of Magetan makes creative ideas to produce new products. Bitter melon which has a bitter taste that is often used as fresh vegetables turned out to contain more properties for health. The puRpose of this study is to analyze marketing strategies and product innovation to add value to making bitter melon chips. This study uses a qualitative method which is a type of research that emphasizes written words and pictures. The results of this study indicate that the business of bitter melon chips is able to create high values ??from bitter melon fruit. Marketing strategies and product innovations in the form of packaging, providing variants of taste and labeling are competitive advantages, creating interest in consumer interest and opening wider markets. making a good business opportunity to maintain competitiveness requires marketing strategies and product innovations so as to be able to appeal to consumers